A Look at Israel's Next Generation of Spiritual and Pastoral Care Providers. (December 2016) - Kopacz, Marek S.; Feldstein, Bruce D.; Allman Asekoff, Cecille; Kaprow, Rabbi Maurice S.; Smith-Coggins, Rebecca
This brief report looks at the demographics as well as professional background and experiences of a sample of Israeli chaplains. An online survey was distributed to 39 Israeli chaplains, yielding a response rate of n = 6 (15.4%). The findings notably highlight the role of women as chaplains, supporting a religiously diverse population, and differing perspectives on the functional role of a chaplain. These findings could help facilitate discussion and future research into chaplaincy services in Israel.